Multicultural Based Education to Minimize Discrimination in Education Practice - Nira Olivia (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2021)
Education is the only way to build an advanced civilization in the welfare of social life. Without quality education, civilization can't progress. The purpose of education is essential so that a person has a personality that is following the values ??in society and culture (Kasan, 2004). Indonesia's very rich natural resources have not been able to be enjoyed and developed so well because one of the main causes is low quality and quality of education for the Indonesian people and the rampant irregularities in the educational institutions themselves. Problems in the world of education are very complex, so they demand to work harder and have a strong enough ability to overcome these educational problems. (Kasan, 2004)The government has issued many policies to minimize the problem of differences in Indonesia, but in practice, this has not been implemented properly at the school level. One way that the Indonesian nation can compete globally is that the practice of education in Indonesia must truly realize multicultural education as a complete force. Indonesia must be built together without mutual suspicion, intolerance, discrimination, and injustice. All students from all backgrounds must get the same opportunity and treatment so that the Indonesian nation can experience renewal. This research provides a practical overview of how education in Indonesia should be managed on a multicultural basis as a whole force. This research also provides a contribution or practical step to macro-level education managers to take policies that are multicultural based and free from the practice of intolerance.